The Role of Consensus Interferon in the Current Treatment of Chronic Hepatitis C Viral Infection - Fish, Eleanor N. (Millennium Medical Publishing, 2008)
The current standard-of-care for chronic hepatitis C viral infection is treatment with pegylated interferon (PegIFN) plus ribavirin for 24 to 48 weeks. Approximately 50% of HCV-infected patients achieve a sustained viral response (SVR) to this treatment. However, the remaining patients either respond during treatment but relapse upon treatment cessation, respond minimally, or do not respond at all. Much research effort has been expended in attempting to predict those patients who will achieve viral eradication with PegIFN/ribavirin treatment, and it is now clear that those who have either a rapid virologic response (RVR) by week 4 of treatment or a complete early virologic response (cEVR, HCV RNA qualitative negative) by week 12 will go on to achieve SVR at very high rates (70%–90%). Several trials have been completed in patients that fail to achieve RVR or cEVR. These trials include strategies of extending duration of therapy, induction regimens, or retreatment with similar and dissimilar alfa interferons. A recent study of 696 genotype 1 patients treated with both PegIFN and weight-based ribavirin revealed that only 1.6% (4/246) of patients without RVR or cEVR achieved SVR. Consensus interferon, a wholly synthetic interferonalfa, is one of the agents that has been utilized in patients that fail treatment with PegIFN/ribavirin. This molecule has been demonstrated to have a very high affinity for the interferon-alfa receptor, and laboratory studies have demonstrated that it has high levels of antiviral activity. In order to optimally utilize consensus interferon, it is important to understand its unique mechanism of action. In addition, the latest research showing the importance of achieving RVR or cEVR should be reviewed, along with strategies for utilizing consensus interferon in re-treatment, or more specifically upon identification of on-treatment failure in historically difficult-to-treat patients.